ORGANIZATION OF DOCTORAL TRAINING AT VILNIUS GEDIMINAS TECHNICAL UNIVERSITY - Pranas Baltrenas (Высшее образование в России)
The article presents an experience in organization and realization of doctoral programs at Vilnius Gediminas Technical University. The goals, peculiarities of organization, scope and content of educational programs, the requirements for applicants are characterized. The author dwells upon the thesis defense procedure. The article is prepared within the framework of TEMPUS project «NETCENG» - New Model of the Third Cycle in Engineering Education Due to Bologna Process in BY, RU, UA. The project “NETCENG” is financially supported by the European Commission. The European Commission is not liable for the content of this publication.